Определение микрохарактеристик воздушного потока в носовой полости при дыхании - Носова, Яна Витальевна; Аврунин, Олег Григорьевич; Хушам Фарук, И. С. (НТУ "ХПИ", 2018)
Статья посвящена определению степени травматизации слизистой оболочки носовой полости с турбулентным воздушным потоком. Прохождение воздуха через верхний носовой ход обеспечивает доставку молекул одоривертора в чувствительные области обонятельного анализатора. Изучение характеристик воздушного потока в верхнем носовом проходе позволяет определить границы пристеночного ламинарного воздушного подслоя и изучить назальную аэродинамику на микроуровне. Турбулентный поток способствует чрезмерному высушиванию слизистой оболочки носовой полости, что приводит к ее морфологической перестройке к субатрофическому процессу. Было обнаружено, что толщина ламинарного подслоя составляет около 1 мм, поэтому участок слизистой оболочки подвергается сушке с увеличением турбулентности течения в местах сужения носовой полости (обонятельной щели).

The aim of the work is to determine the degree of traumatization of the mucous membrane of the nasal cavity by turbulent air flow. It should be noted that it is especially important to determine in the narrowing of the nasal cavity (olf actory gap), where the mucous membrane is subjected to drying with increasing turbulence of the air flow. Achieving this goal will increase the effectiveness of diagnosis and treatment of respiratory and olfactory disorders and will help to identify the pathogenesis of chronic rinological diseases. An important characteristic of nasal breathing is the distribution of air flow rates along the sections of the nasal cavity. When analyzing the existing approaches, it was determined that the main method of studying the aerodynamics of the nasal cavity is rhinomanometry. However, there is not always a clear correlation between anatomical and functional indicators, as well as subjective feelings of the patient and rhinomanometric data. The passage of air through the upper nasal passage ensures the delivery of odorivector molecules to sensitive areas of the olfactory analyzer. The study of the characteristics of the air flow in the upper nasal passage allows us to determine the boundaries of the near-wall laminar air sublayer and to study nasal aerodynamics at the micro level. Turbulent flow contributes to the excessive drying of the mucous membrane of the nasal cavity, leading to its morphological rearrangement towards the subatrophic process. It was found out that the thickness of the laminar layer is of the order of 1 mm, therefore the protuberances of the mucosa are subjected to drying with increasing turbulence of the flow at the sites of narrowing of the nasal cavity (olfactory gap). The prospect of work is the study of the characteristics of the boundary layer in typical pathologies in various respiratory regimes, which will improve the efficiency of diagnosis and treatment of respiratory and olfactory disorders and will help to identify the pathogenesis of chronic rinological diseases.
Determination of microcharacteristics of air flow in the nasal cavity during breathing
Keywords: обонятельная щель; ламинарный пограничный слой; слизистая оболочка; носовая полость; турбулентный поток; laminar air sublayer; mucous membrane; turbulent flow